EFFORTS TO INCREASE THE SHELF LIFE OF RED NILE FISH MEATBALLS (Oreochromis niloticus) BY ADDING LIQUID SMOKE - Ardi Lesmana Saputra; Rizky Muliani Dwi Ujianti; Iffah Muflihati; Fafa Nurdyansyah; Mega Novita (Universitas Mataram, 2026)
Red tilapia fish meatballs are a popular processed fishery product because they have a taste liked by various groups and are relatively affordable, making them accessible to all. However, red tilapia fish meatballs have a short shelf life, so safe, natural preservation methods are needed; one is liquid smoke. This study aims to determine the effects of soaking time and the addition of liquid smoke on the shelf-life of red tilapia fish meatballs (Oreochromis niloticus) during a shelf-life test. This study used a Completely Randomized Design (CRD) with two treatment factors: soaking time (30 minutes and 45 minutes) and liquid smoke at 1.5% and 3%. Analysis of red tilapia fish meatballs included testing for water content, ash content, total acid, total phenols, texture, a sensory test, and a shelf-life test. The results showed that the addition of liquid smoke significantly increased ash content and total acid, decreased water content, improved texture, and increased the shelf life of fish meatballs. The total acid analysis yielded values of 0.14%-0.36%, and the total phenol content yielded values of 0.06%-0.15%. Meanwhile, the analysis of fish meatball products included texture characteristics such as hardness (254.8-351.4), cohesiveness (0.87-0.93), and springiness (0.83-1.00). The moisture content analysis yielded values of 5.07%-5.73%, and the ash content analysis yielded values of 1.85%-2.82%. Based on the research results, liquid smoke is an effective natural preservative that improves the quality and shelf life of red tilapia fish meatballs.